Role of virus infection in asthma 1 - Johnston, Sebastian (Henry Stewart Talks, 2011)
Role of viruses in asthma exacerbations, Huge clinical problem unmet by current therapies, Viruses major cause in all age groups, Deficient anti-viral immunity in asthma, Potential therapies; specific anti-virals and broad-spectrum approaches